ショウワ キチ フキンサン ガンセキ ノ ゼッタイ ネンダイ ト ソノ コウサツ - 矢内, 桂三; ヤナイ, ケイゾウ; 植田, 良夫; ウエダ, ヨシオ; YANAI, Keizo; UEDA, Yoshio (国立極地研究所, 1974)
P(論文) The K-Ar age determination on micas from the metamorphic rocks and granites in the Ongul Islands and Lang Hovde areas gave the following results: Metabasites 463, 467, 515, 517, 533 and 539 m.y. Biotite gneiss 560 m.y. Hornblende gneiss 485 m.y. Microcline granite 399 m.y. Biotite from microcline granite shows the youngest age in the areas of the report. This age agrees well with the field evidence that the granites are discordant dikes in the metamorphic rocks. On the basis of the ages hitherto determined for the metamorphic and granitic rocks in the Liitzow-Holm Bay coast and the Yamato Mountains some considerations are given to the metamorphic events. departmental bulletin paper